IR-transparent MgO-Y2O3 ceramics by self-propagating high-temperature synthesis and spark plasma sintering. Issue 10 (July 2020) - Permin, D.A.; Boldin, M.S.; Belyaev, A.V.; Balabanov, S.S.; Novikova, A.V.; Koshkin, V.A.; Murashov, A.A.; Ladenkov, I.V.; Popov, A.A.; Lantsev, E.A.; Khamaletdinova, N.M.
Abstract: A glycine–nitrate self-propagating high temperature synthesis (SHS) was developed to produce composite Y2 O3 –MgO nanopowders. Based on the thermodynamic calculations a 0.25YMg2 (NO3 )7 -0.75NH2 CH2 COOH precursor composition was selected to prepare low agglomerated uniform composite yttria-magnesia powder. Near full dense composite ceramics were fabricated based on the prepared powders by the spark plasma sintering method. IR-transmittance and hardness of the Y2 O3 –MgO ceramics were studied in correlation with sintering conditions. The best transmittance of 80.9%@5 μm and Hv = 10.2 GPa were measured for the sample obtained at 1150 °C.